The Characteristics of Song Copyright in Bank Debt Guarantees - Elyana Novira; Prima Resi Putri; Briggs Samuel Mawunyo Nutakor (Faculty of Law, Universitas Jenderal Soedirman, 2023)
By focusing on the Indonesian context and based on Law Number 28 of 2014 concerning Copyright, this study analyzes the characteristics of copyright to songs as assets that can be pledged as collateral, as well as the impacts and implications of copyright utilization in the financial sector and creative industries. The results of the research show that copyright has the potential to be used as collateral in debt transactions at banks. Factors such as the economic value of the work, exclusive control, legal protection, and regular income allow copyright to be used as collateral. Copyright law regulates the process of guaranteeing, utilizing, and executing copyright as security. The use of copyright as collateral has a positive impact on the financial sector and the creative industry. Diversification of bank portfolios, easier access to finance for creative industry players, as well as increased innovation and creativity are the identified impacts. However, there are also challenges, such as complex copyright value assessments and potential conflicts of interest between rights owners and financial institutions.